2010
DOI: 10.1111/j.1582-4934.2009.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical load modulates chondrogenesis of human mesenchymal stem cells through the TGF‐β pathway

Abstract: This study investigated the effect of mechanical load on human mesenchymal stem cell (hMSC) differentiation under different exogenous transforming growth factor-β1 (TGF-β1) concentrations (0, 1 or 10 ng/ml).The role of the TGF-β signalling pathway in this process was also studied. Human MSCs were seeded into fibrin-biodegradable polyurethane scaffolds at a cell density of 5 × 106 cells per scaffold and stimulated using our bioreactor. One hour of surface motion superimposed on cyclic compression was applied on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
177
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(186 citation statements)
references
References 37 publications
6
177
1
2
Order By: Relevance
“…Therefore identifying expansion and differentiation conditions that promote a more chondrogenic phenotype is critical to enhancing their utility for cartilage tissue engineering applications. Differentiation conditions that have been shown to promote the chondrogenic potential of MSCs include a low oxygen (5%) microenvironment (Khan et al 2007;Buckley et al 2010a;Meyer et al 2010), various combinations of growth factors (Mastrogiacomo et al 2001;Sakimura et al 2006;Hennig et al 2007;Diekman et al 2010;Buxton et al 2011) and mechanical signals (Huang et al 2005;Mauck et al 2007;Huang et al 2010a;Huang et al 2010b;Kelly and Jacobs 2010;Li et al 2010; Thorpe et al 2010;Haugh et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore identifying expansion and differentiation conditions that promote a more chondrogenic phenotype is critical to enhancing their utility for cartilage tissue engineering applications. Differentiation conditions that have been shown to promote the chondrogenic potential of MSCs include a low oxygen (5%) microenvironment (Khan et al 2007;Buckley et al 2010a;Meyer et al 2010), various combinations of growth factors (Mastrogiacomo et al 2001;Sakimura et al 2006;Hennig et al 2007;Diekman et al 2010;Buxton et al 2011) and mechanical signals (Huang et al 2005;Mauck et al 2007;Huang et al 2010a;Huang et al 2010b;Kelly and Jacobs 2010;Li et al 2010; Thorpe et al 2010;Haugh et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The results of pervious study showed that compressive loading increased in TGF-β1 gene expression [12]. In the culture medium without TGF-β1, mechanical loading stimulated gene and protein expression of TGF-β1 and TGF-β3 [22]. TGF-β signaling may magnify the sensitivity of cells to mechanical forces by increasing of transcriptional factors such as SOX9 as a master gene of chondrgenesis.…”
Section: Discussionmentioning
confidence: 94%
“…ColVI trimer formation occurs intracellularly before being secreted into the PCM for microfibrillar networking via BGN or DCN (Bruns et al, 1986;Engvall et al, 1986;Wiberg et al, 2003;DiMicco et al, 2007) and is maintained at low levels of transcription (DiMicco et al, 2007;Vigfusdottir et al, 2010). DCN is a ubiquitous proteoglycan, consisting of a core protein with a single chondroitin sulphate (Li et al, 2010) or dermatan sulphate (Knudson et al, 1996) side chain. It interacts with multiple collagens to create functional bridges between the PCM and surrounding ECM, and is involved in controlling fibrillogenesis and growth factor bioavailability (Chen et al, 2009;Lewis et al, 2010;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These growth factors cause PCM accumulation during chondrogenesis in a concentration dependent manner (Mehlhorn et al, 2006;Lee et al, 2010;Li et al, 2010). Sequestration of growth factors immediately surrounding the cell allows for specifically stimulated responses, being released mechanically or enzymatically from their associated PG for presentation to the cell membrane.…”
Section: Jd Twomey Et Al Colvi and Dcn In Chondrogenic Hmsc Biophysicsmentioning
confidence: 99%